Comparative proteome analysis revealed potential biomarkers and the underlying immune mechanisms in Vibrio-resistant hybrid grouper, Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ - Abu Aziz, Nurhikmah; Christianus, Annie; Wan Solahudin, Wan Mohd Syazwan; Ismail, Intan Safinar; Low, Chen‐Fei (John Wiley and Sons, 2024)
Vibrio alginolyticus is the causative agent of vibriosis, a common bacterial infection in grouper aquaculture that is associated with the development of haemorrhagic and non-haemorrhagic ulcerations on the fish. In the present study, comparative proteome analysis was performed on serum samples from Vibrio-resistant and Vibrio-susceptible grouper. Samples were analysed using high-throughput LC-MS/MS and identified 2770 unique peptides that corresponded to 344 proteins. Subsequent analysis identified 21 proteins that were significantly up-regulated in the resistant group compared to the control and the susceptible groups. Those proteins are associated with immunostimulatory effects, signalling and binding cascade, metabolism, and maintaining tissue integrity and physiological condition. Besides, potential protein biomarkers related to the immune system were identified, which could be associated with the disease-resistant phenotype. These data provide insights into the underlying immune mechanism of hybrid groupers upon Vibrio sp. infection.